A trajectory of light: The pedagogical inherence in the professional practice of the University Laboratory of Lighting Design (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
With over 25 years of experience in his career, Denílson Marques from São Paulo defines himself as a lighting designer and as a professional in the practice of lighting design in a university laboratory. Speaking of his shows that incorporate technical and aesthetic knowledge, in addition to his role in training students, as well as his search for knowledge that diversify his education, he understands his work as inherent to a pedagogical action shared with students from an undergraduate course in performing arts. In an interview given in May 2021, Denílson recounts his trajectory of light, his learning processes, comments on the support received and his understanding of the role he plays in the Teatro Laboratório of the University of São Paulo, USP.